Development of legal highs. (2nd March 2015) - Wasunna, Brenda; Thomas, Emily; Morgan, Sally
Abstract: New psychoactive substances (NPS) or 'legal highs' are defined as unregulated psychoactive substances including synthetic and/or plant derived substances (marketed as research chemicals, party pills and herbal highs) that are intended to mimic the effects of controlled drugs. Psychiatric services around the country are seeing a rise in the use of NPS complicating mental health presentations. The challenge surrounding these substances is the fact that they are not under the international drug control system and are proving to have a detrimental health effect on users. This article reviews the current literature on this subject and discusses some of the most common examples of NPS and their potential effects on mental health.